Evolution of maternal and neonatal outcomes before and after the adoption of the IADPSG/WHO guidelines in Belgium: A descriptive study of 444, 228 pregnancies. Issue 4 (April 2022) - Oriot, Philippe; Leroy, Charlotte; Van Leeuw, Virginie; Philips, Jean Christophe; Vanderijst, Jean François; Vuckovic, Aline; Costa, Elena; Debauche, Christian; Chantraine, Frederic
Abstract: Objectives: To appraise adverse pregnancy outcomes after the adoption of IADPSG/WHO guidelines in Belgium. Methods: A retrospective study of the Center for Perinatal Epidemiology registry was conducted. Demographic changes and adverse pregnancy outcomes were compared between a pre- and post-guideline period in women with and without hyperglycemia in pregnancy (HIP). Adjusted odds ratios with a 95% confidence interval (CI) were used to compare maternal and neonatal outcomes controlling for potential confounders (maternal age, body mass index (BMI), hypertension, parity, and multiple births). Results: The prevalence of HIP increased (6.0%–9.2%). In the overall population regardless of glycemic status, gestational weight gain (12.3 ± 5.7 vs 11.9 ± 5.8; p < 0.001), hypertension (0.92; 95% CI, 0.89–0.94; p < 0.001), and neonatal intensive care unit/special care nursery (0.89; 95% CI, 0.87–0.91; p < 0.001) decreased despite increasing maternal age and pre-pregnancy BMI. Emergency cesarean section rates (1.07; 95% CI, 1.05–1.09; p < 0.001) increased, but not in the HIP population (1.02; 95% CI, 0.95–1.10; ns ). The overall incidence of preterm birth (1.09; 95% CI, 1.06–1.12; p < 0.001), stillbirth (1.10; 95% CI, 1.01–1.21; p < 0.05), and perinatal mortality (1.10; 95% CI, 1.01–1.19; p < 0.05) increased, except in the HIP population (1.03; 95% CI, 0.95–1.11; ns), (1.04; 95% CI, 0.74–1.47; ns) and (1.09; 95% CI, 0.80–1.49; ns), respectively. The overall incidence of small- for-gestational-age remained unchanged (0.99; 95%CI, 0.97–1.01; ns) regardless of glycemic status. In the HIP population, large-for-gestational age (0.90; 95% CI, 0.84–0.95; p < 0.001) and macrosomia (0.84; 95% CI, 0.78–0.92; p < 0.001) decreased. Conclusion: After the implementation of IADPSG/WHO guidelines, the prevalence of HIP increased by 53.7% and the incidence of major HIP-related pregnancy complications appears to be lower. However, we cannot conclude that the reduction of LGA-macrosomia is due to a better management of diabetes or due to greater recruitment of women with mild HIP associated with a lower risk of obstetrical complications. Abstract : Pregnancy complications; IADPSG/WHO criteria; Diabetes; Gestational diabetes mellitus; Hyperglycemia in pregnancy; Epidemiology; Prevalence.